2013
DOI: 10.1016/j.yqres.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

A 30,000 yr Record of land-ocean interaction in the eastern gulf of Guinea

Abstract: A 30,000 yr dinocyst and pollen record from the eastern equatorial Atlantic (off Cameroon) has been investigated in order to identify land–ocean linkages during the last deglacial transition. A strong correlation between the abundance of Brigantedinium spp. and the Ca/Fe ratio during the last glacial period suggests enhanced marine productivity in association with cool seawater temperatures and nutrient input linked to coastal upwelling and/or a proximal river mouth. Dry conditions are recorded on the adjacent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…At that time, the TR was characterized by a wider latitudinal extension of up to several degrees poleward (Stager et al, 2011;Arbuszewski et al, 2013;McGee et al, 2014). Previous dinocyst studies showed that the AHP was characterized by the gradual bloom of thermophile (S. mirabilis) and low-salinity (O. aguinawense) species, induced by strengthened river discharges from the beginning of the Holocene (Dupont and Behling, 2006;Kim et al, 2010;Marret et al, 2013).…”
Section: The Early Holocene and The African Humid Periodmentioning
confidence: 96%
See 1 more Smart Citation
“…At that time, the TR was characterized by a wider latitudinal extension of up to several degrees poleward (Stager et al, 2011;Arbuszewski et al, 2013;McGee et al, 2014). Previous dinocyst studies showed that the AHP was characterized by the gradual bloom of thermophile (S. mirabilis) and low-salinity (O. aguinawense) species, induced by strengthened river discharges from the beginning of the Holocene (Dupont and Behling, 2006;Kim et al, 2010;Marret et al, 2013).…”
Section: The Early Holocene and The African Humid Periodmentioning
confidence: 96%
“…Reconstructions of late Quaternary and Holocene palaeoceanographic changes at the western African margin and associated Benguela upwelling system have identified orbital and suborbital controls on sea-surface and continental environmental conditions (Holzwarth et al, 2007). More specifically, several palynological studies carried out in the equatorial eastern Atlantic Ocean, combining analysis of pollen grains and cysts of dinoflagellates (dinocysts), have provided a wealth of information on land-sea interactions in the intertropical region, through investigation of sea-surface and terrestrial vegetation changes over the last climatic cycles (Shi et al, 1998;Marret and Zonneveld, 2003;Dupont and Behling, 2006;Marret et al, 2008Marret et al, , 2013Kim et al, 2010;Bouimetarhan et al, 2012). However, these above-mentioned studies mainly focused on the comparison between periods of extreme climatic conditions, such as the Last Glacial Maximum (Mix et al, 2001) and the Holocene climatic optimum, showing that higher primary productivity conditions occurred during glacial periods in response to an increase in upwelling activity while enhanced freshwater discharges from the continent occurred during interglacials.…”
Section: Introductionmentioning
confidence: 99%
“…Transitions between forest and savannah have been tracked through the last c. 1 Ma in tropical West Africa by 15 offshore pollen records (Sowunmi 1981;Dupont et al 1989;Bengo & Maley 1991;Dupont & Agwu 1992;L ezine & Vergnaud-Grazzini 1993;Fr edoux 1994;Dupont & Weinelt 1996;Shi & Dupont 1997;Dupont et al 1998;Jahns et al 1998;Shi et al 2001;Marret et al 2013;Dalibard et al 2014;Vall e et al 2014) and several terrestrial records (Maley 1991;Elenga et al 1994;Maley & Brenac 1998;Salzmann et al 2002) of which only one record is older than 35 ka BP (Lake Bosumtwi, Ghana). The fossil pollen record obtained from Lake Bosumtwi is unique to tropical West Africa, and to date covers the last c. 500,000 years of the 1 Ma sediment core that was recovered (Koeberl et al 2007;Miller et al 2016).…”
Section: Forest-savannah Transitions Through Timementioning
confidence: 99%
“…Three major sources of fan material can be distinguished: (1) dissolved and suspended supply from the Congo River consisting of products of weathering of the West African continental hinterland and river phytoplankton productivity, (2) atmospheric dust and (3) microorganism remains (Jansen, 1990). The sediments of the deep-sea fan system are therefore an important source of information for reconstructing the geological history of the margin (Savoye et al, 2009), the conditions on the continent (Gingele et al, 1998;Jahns et al, 1996;Dalibard et al, 2014), the relationship between atmospheric and oceanographic circulation (Schneider et al, 1994;Dupont et al, 1999), the interactions between the Congo River and the tropical Southern Atlantic circulation (Jansen and van Iperen, 1991;Uliana et al, 2002) as well as the variations of primary productivity on the Congo-Angola margin (Schneider et al, 1997;Dale et al, 2002;Marret et al, 2008Marret et al, , 2013Hardy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%